End-of-Life Treatment of Poly(Vinyl Chloride) and Chlorinated Polyethylene by Dehydrochlorination in Ionic Liquids - Glas, Daan; Hulsbosch, Joris; Dubois, Philippe; Binnemans, Koen; De Vos, Dirk E. (ChemSusChem, 2014)
There is an urgent need for green technologies to remove halogens from halogenated polymers at the end of their lifetime. Ionic liquids (ILs) were used to dehydrochlorinate and/or dissolve the chlorinated polymers poly(vinyl chloride) (PVC) and chlorinated polyethylene (CPE). The dehydrochlorination activity of an IL depends mainly on its anion and is related to the high hydrogen‐bond‐accepting ability (β value) of the anion. Different phosphonium ILs successfully dissolve and dehydrochlorinate PVC and CPE at temperatures from 80 °C. PVC is dehydrochlorinated up to 98 % after 60 min in tetrabutylphosphonium chloride ([P4444][Cl]) at 180 °C. PVC pieces stabilized by calcium stearate (4 mm3) are dehydrochlorinated more slowly; conversions of 85 and 96 % are reached after 1 and 8 h, respectively. Smaller pieces are dehydrochlorinated faster. High loadings, for example, 0.3 g stabilized PVC in 0.5 g IL, can be applied with only a minor loss of conversion. [P4444][Cl] proved to be stable during several consecutive reactions; after each run more than 99 % of the IL can be recovered. The structure of the dehydrochlorinated PVC was studied by 13C cross‐polarization magic‐angle spinning NMR and FTIR spectroscopy; the removal of Cl and the formation of double bonds were confirmed. Carefully dehydrochlorinated CPE was processed further by acyclic diene metathesis depolymerization with ethylene and the Hoveyda–Grubbs second‐generation catalyst to yield α,ω‐dienes such as 1,5‐hexadiene and 1,6‐heptadiene. Easy as PVC: Thermally stable phosphonium ionic liquids (ILs) are the solvent and catalyst for the dehydrochlorination of polymers such as poly(vinyl chloride) (PVC). The true dissolution of PVC by ILs can facilitate the complete HCl elimination from the polymer chains. The dehydrochlorinated materials are characterized in detail and some of them are successfully depolymerized in a catalytic reverse acyclic diene metathesis (ADMET) process.